ARTERIAL HAEMODYNAMIC PARAMETERS LINKED TO ARTERIAL PULSATILITY, EXCESS WAVE PROPAGATION AND COGNITIVE FUNCTION. (June 2022) - Jordan, Andrew N.; Aizawa, Kunihiko; Gooding, Kim M.; Llewellyn, David; Casanova, Francesco; Mawson, David M.; Gates, Phillip E.; Adingupu, Damilora D.; Elyas, Salim; Hope, Suzy V.; Strain, W. David; Clark, Chris E.; et al.
Abstract : Objective: Hypertension is associated with the development of cognitive impairment and dementia in an ageing population. Aortic stiffness and alterations in central artery haemodynamics could intensify the penetration of excess wave energy into the cerebral circulation, damaging the microvasculature in addition to age-associated vascular changes. We aimed to determine whether haemodynamic parameters linked to arterial pulsatility and excess wave propagation was associated with cognitive function in a sample of normotensive and hypertensive individuals. Design and method: We studied 35 treatment-naïve patients with stage II/III hypertension (HT: 63.8 ± 7.4yrs, 19F, SBP 175.6 ± 16.8 mmHg) and 35 age-, sex- and body mass index-matched normotensive individuals (NT: SBP 127.2 ± 8.2 mmHg). Indices of excess pressure including excess pressure integral (INTXSP) and peak excess pressure (MAXXSP) were obtained by radial artery tonometry. Aortic forward compression wave intensity (FCWI) and aortic pulse wave velocity (aPWV) were estimated as proposed by Hughes et al (Front Physiol. 2020). A battery of cognitive examination tests was administered including Addenbrooke's Cognitive Examination-III (ACE), Mini-Mental State Examination (MMSE), Trail making test part A (TMT-A) and B (TMT-B). Results: Both INTXSP (9.2 ± 2.7 vs 5.4 ± 1.2 mmHg s) and MAXXSP (54.1 ± 12.8 vs 33.4 ± 5.9 mmHg) were significantly higher in HT compared to NT (p < 0.001). Additionally, FCWI [14.9 (12.0–20.0) vs 8.0 (6.8–9.3) x105 W/m 2 ] and aPWV (7.2 ± 1.7 vs 4.5 ± 0.8 m/s) were significantly greater in HT compared with NT (p < 0.001). Higher INTXSP was associated with poorer ACE (rs = -0.310, p = 0.009), longer TMT-A (r = 0.409, p < 0.001) and TMT-B (r = 0.380, p = 0.001). Similarly, higher MAXXSP was associated with poorer ACE (rs = -0.343, p = 0.004), longer TMT-A (r = 0.397, p = 0.001) and TMT-B (r = 0.330, p = 0.006), and greater aPWV was associated with poorer ACE (rs = -0.331, p = 0.005), longer TMT-A (r = 0.397, p = 0.001) and TMT-B (r = 0.324, p = 0.007). Higher FCWI was associated with longer TMT-A (rs = 0.378, p = 0.002) and TMT-B (rs = 0.260, p = 0.038), and showed a trend to be associated with poorer ACE (rs = -0.238, p = 0.054). None of the haemodynamic indices was associated with MMSE. Conclusions: Haemodynamic parameters linked to excess arterial wave propagation are associated with poorer cognitive function. These observations reveal a potential mechanism linking hypertension and cognitive impairment, and reinforce the importance of blood pressure control to reduce cognitive impairment risk.